Acoustic metamaterial for image detection - Abdul Hamid, Siti Zaleha; Daud, Nur Farah Hanis; Abdul Rahim, Herlina; Abdul Rahim, Ruzairi (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2018)
Image detection is important especially in medical for non destructive examination. Early development of image detection used high frequency for clearer image and caused heat development. Hence, there is a need to design metamaterial that can detect the image with lower frequency. This study focused on holey structured of three dimensions (3D) metamaterial. Methodology for this study can be divided into three parts which are metamaterial design, metamaterial testing, and performance analysis. The hole size, type of material and thickness of metamaterial designed will be varied for performance comparison. The image produce at the output plane of the metamaterial is clearly with the smallest scale size of hole which is 1.5 mm and the thickness of the metamaterial at 130 mm is equal with the operating wavelength. The device perfectly operated at lower frequency of 2.6 kHz.